2022
DOI: 10.1017/s136898002200180x
|View full text |Cite
|
Sign up to set email alerts
|

Eating contexts and their associations with socio-demographic factors in Brazilian adolescents (EVA-JF Study)

Abstract: Objective: To describe the eating contexts and estimate their associations with sociodemographic factors in a sample of Brazilian adolescents. Design: Cross-sectional study. We used an exploratory questionnaire about eating contexts (encompassing regularity of meals, places where they occur, and if they take place with attention and in company), which was submitted to cluster analysis. Subsequently, three clusters were identified: cluster 1, “appropriate eating contexts at breakfast, lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Contrary to our findings, a few investigations discovered no association between demographic and lifestyle variables with overweight or obesity ( 7 , 20 ). A Brazilian study observed sociodemographic characteristics (such as the mother's education level, age range, and gender) were linked to inappropriate eating situations at breakfast and/or dinner ( 46 ). Our results are compatible with several studies ( 20 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, a few investigations discovered no association between demographic and lifestyle variables with overweight or obesity ( 7 , 20 ). A Brazilian study observed sociodemographic characteristics (such as the mother's education level, age range, and gender) were linked to inappropriate eating situations at breakfast and/or dinner ( 46 ). Our results are compatible with several studies ( 20 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ALTS questionnaire assessed eating habits by 10 items (38)(39)(40)(41)(42)(43)(44)(45)(46)(47). "Participants were asked frequency of breakfast, fizzy drinks (including soft drinks), vegetables, fruits, and dairy products, donuts and cakes, candy and chocolate, energy drinks, and fast foods per week.…”
Section: Eating Habits Assessmentmentioning
confidence: 99%